Analisis Budget Kas Dalam Meningkatkan Likuiditas dan Profitabilitas Perusahaan - Elaksmi, Lydia Resti; Djuharni, Darti (Akutansi Bisnis & Manajemen ( ABM ), 2019)
The purpose of the study to find out how the cash budget implementation at metal company UD Lancar Jaya, Tulungagung in increasing liquidity and profitability. The research method used is case study research. The researcher conducts financial ratio analysis consisting of analysis of liquidity and profitability through financial statements, namely the income statement and balance sheet for 2015-2017 and prepares financial report projections in 2018. The analysis shows that the company faces the problem that is using inefficient funds